Encountering the mystery : understanding Orthodox Christianity today - Bartholomew I, Ecumenical Patriarch of Constantinople, 1940- (New York : Doubleday, 2008)
The spiritual leader of Orthodox Christianity chronicles the history, culture, traditions, and tenets of his faith, tracing the two-thousand-year evolution of the faith, the schisms that led to its split with Western Christianity, and its doctrine and liturgy
Foreword / Kallistos Ware -- Biographical note / John Chryssavgis -- Historical perspectives : the Orthodox Church and the Ecumenical Patriarchate -- Song and space : art, architecture, and liturgy -- The gift of theology : basic principles and perspectives -- Vocation of love : monasticism as choice and calling -- Spirituality and sacraments : prayer and the spiritual life -- The wonder of creation : religion and ecology -- Faith and freedom : conscience and human rights -- Transforming the world : i. social justice ; ii. religion and society ; war and peace -- Epilogue: The hope that lies within
Includes bibliographical references (pages 251-252) and index
Keywords: Orthodox Eastern Church; Orthodox Eastern Church